PENERAPAN BAHAN AJAR BERBASIS ADVANCE ORGANIZER MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MURDER PADA SISWA KELAS XI SEMESTER 1 DI SMA NEGERI 3 SOLOK - Riri Awalia Apersa (PILLAR OF PHYSICS EDUCATION, 2014)
Achievement of learning outcomes will be achieved by students if the optimal instructional materials used have a concept of meaningfulness between concepts with each other and create a fun learning environment, here by increasing the student’s motivation. To achieve this goal, the learning type Cooperative  MURDER  is a model for effective learning to improve student learning outcome.Therefore , this study aimed to examine the effect of the use of teaching materials based Advance Organizer through cooperative learning model MURDER on student learning outcomes SMA Negeri 3 Solok. This research is quasi- experimental. Sampling was done by purposive sampling. Based on the research that has been done, it can be concluded that there is a significant difference between the learning outcomes of students who use teaching materials based on the Advance Organizer cooperative learning model MURDER on the real level of 0.05